2005
DOI: 10.1593/neo.04586
|View full text |Cite
|
Sign up to set email alerts
|

Array-Based Comparative Genomic Hybridization Identifies Localized DNA Amplifications and Homozygous Deletions in Pancreatic Cancer

Abstract: Pancreatic cancer, the fourth leading cause of cancer death in the United States, is frequently associated with the amplification and deletion of specific oncogenes and tumor-suppressor genes (TSGs), respectively. To identify such novel alterations and to discover the underlying genes, we performed comparative genomic hybridization on a set of 22 human pancreatic cancer cell lines, using cDNA microarrays measuring approximately 26,000 human genes (thereby providing an average mapping resolution of <60 kb). To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
166
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(173 citation statements)
references
References 46 publications
6
166
1
Order By: Relevance
“…58,60 Homozygous loss of DKK3 has been reported in pancreatic cancer. 61 Our study implicates DKK3 in differentiation and proliferation of neuroblastic tumors and shows a regulation by the MYCN oncogene.…”
Section: Discussionmentioning
confidence: 61%
“…58,60 Homozygous loss of DKK3 has been reported in pancreatic cancer. 61 Our study implicates DKK3 in differentiation and proliferation of neuroblastic tumors and shows a regulation by the MYCN oncogene.…”
Section: Discussionmentioning
confidence: 61%
“…These studies revealed that the TRRAP locus at chromosome 7q22.1 is amplified in human cancer cell lines (Bashyam et al, 2005) and human pancreatic adenocarcinoma (Loukopoulos et al, 2007). In addition, few mutational screens in a limited number of human cancers identified somatic mutations in TRRAP gene in several human malignancies including cancers of ovaries, stomach, large intestine and lung (Cosmic database; www.sanger.ac.uk/ genetics/CGP/cosmic/).…”
Section: Possible Roles Of Trrap In Human Malignanciesmentioning
confidence: 99%
“…[5][6][7] TUSC3 (tumor suppressor candidate 3), originally named N33, was identified as a potential tumor suppressor gene in prostate cancer 8,9 and is located on chromosome band 8p22. Known homozygous deletions of this region in pancreatic cell lines 10,11 and prostate cancer cell lines 12,13 contain no other cancer-related genes except TUSC3, although mutations of the TUSC3 coding sequence have not been observed. Through a systematic screening of this region on 8p22, we recently observed that TUSC3 is significantly down-regulated in high-grade ovarian cancer and may have prognostic significance.…”
Section: Introductionmentioning
confidence: 97%